Geospatial Analysis of Urban Expansion Using Remote Sensing Methods and Data: A Case Study of Yangtze River Delta, China. (14th August 2020) - Sun, Wei; Shan, Jie; Wang, Zhiming; Wang, Lei; Lu, Dianmei; Jin, Zhifeng; Yu, Kun
Abstract : Land use in the Yangtze River Delta in 2000 and 2017 was classified by the visual interpretation of Landsat satellite images. Then, these images were overlain with economic and physical geographical data to analyze the urban spatial expansion pattern and its physical constraints and socioeconomic influence factors by employing a combination of transition matrix analysis, expansion intensity indices, and equal-fan analysis. The results showed that from 2000 to 2017, there was a significant increase in built-up areas in the region, with rapid expansion in the core area. The northern and southern parts of the Yangtze River Delta experienced different urban spatial expansions, with a higher scale and rate in the cities along the Yangtze River and the coast in Jiangsu Province in the north than in Zhejiang Province in the south. Cities expanded towards megacities or hubs along the Yangtze River or the coast, indicating that urban expansion is influenced by preferential policies and urban planning factors in addition to the spillover effects of neighboring cities and the adjacency to seas or large rivers. Finally, urban expansion is significantly constrained by elevation, with cities at lower elevations or in flat terrain undergoing more rapid urban expansion and development.